Efficient sweep buffering in swept source optical coherence tomography using a fast optical switch - Dhalla, Al-Hafeez (Optical Society of America, 2012)
We describe a novel buffering technique for increasing the A-scan rate of swept source optical coherence tomography (SSOCT) systems employing low duty cycle swept source lasers. This technique differs from previously reported buffering techniques in that it employs a fast optical switch, capable of switching in 60 ns, instead of a fused fiber coupler at the end of the buffering stage, and is therefore appreciably more power efficient. The use of the switch also eliminates patient exposure to light that is not used for imaging that occurs at the end of the laser sweep, thereby increasing the system sensitivity. We also describe how careful management of polarization can remove undesirable artifacts due to polarization mode dispersion. In addition, we demonstrate how numerical compensation techniques can be used to modify the signal from a Mach-Zehnder interferometer (MZI) clock obtained from the original sweep to recalibrate the buffered sweep, thereby reducing the complexity of systems employing lasers with integrated MZI clocks. Combining these methods, we constructed an SSOCT system employing an Axsun technologies laser with a sweep rate of 100kHz and 6dB imaging range of 5.5mm. The sweep rate was doubled with sweep buffering to 200 kHz, and the imaging depth was extended to 9 mm using coherence revival. We demonstrated the feasibility of this system by acquiring images of the anterior segments and retinas of healthy human volunteers.